An overview of natural herbal extracts and compounds for combating porcine epidemic diarrhea virus - Wang, Liyan; Bo, Zongyi; Sun, Liumei (Frontiers in Veterinary Science, 2025)
Porcine epidemic diarrhea virus (PEDV) is the etiological agent responsible for the acute infectious intestinal disease known as porcine epidemic diarrhea (PED), which results in severe diarrhea in piglets and causes substantial economic losses to the global swine industry. Currently, no specific therapeutic agent is available for the clinical treatment of PEDV, highlighting the urgent need to screen antiviral compounds and investigate antiviral mechanisms to develop effective antiviral therapies. Using active natural ingredients in animal husbandry represents a significant contemporary trend. Natural herbal products offer numerous advantages, including abundant availability, diverse biological activities, and low toxicity and side effects, as well as a reduced likelihood of developing drug resistance. These attributes position them as valuable resources for the development of effective anti-PEDV drugs. This paper provides a comprehensive review of the current research on the inhibitory effects of herbal monomers (isolated compounds), single-herb extracts, and compound herbal formulations (derived from research) against PEDV. The aim is to establish a theoretical foundation for the screening and development of therapeutic and prophylactic agents targeting PEDV.